PENGARUH PERSEPSI KONSUMEN MENGENAI TINGKATAN ARTI MEREK TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS MEREK PADA PRODUK THE BODY SHOP YOGYAKARTA - Dian Irma Aprianti (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2016)
The main objective of this study is to test empirically the direct effect of the consumer’s on six dimensions of the brand level, and direct effect through customer;s satisfaction as an intervening variable on brand loyalty. The primary data of this study was received from customers of the body shop, that collected by field survey, the result show that consumer’s perception on six dimensions of brand level had a positive and significant relation to customer’s satisfaction and brand loyalty, and by using partial mediating method can be concluded that the costumer’s satisfaction works as intervening variable to the relation between consumer’s perception on six dimensions of brand level to brand loyalty. This result indicates that customer’s brand loyalty happens as the accumulation of customer’s satisfaction.